Mechanical Design for Track Robot Climbing Stairs - Rastan, Homayoun (Université d'Ottawa / University of Ottawa, 2011)
The purpose of this study was to find the best robot configuration for climbing and descending stairs, in addition to traveling on flat surfaces. Candidate robot types were analyzed to find the most suitable one for further study, based on stability, size, and energy consumption. Based on these considerations, the non-variable configuration tracked robot type was selected. The basic robot parameters (minimum track size, comparison of tracks with grousers vs. tracks without grousers, track angle of attack) were determined using static analysis methods and using North American standards for the stair geometry. Dynamic analysis methods were then employed to refine the geometry and ensure the stability of the robot when climbing and descending stairs. The final design was then simulated in Matlab to profile the device's velocity, acceleration, and power consumption during the stair climbing and descending phases. A prototype robot was constructed. The results of this study show that a non-variable tracked robot can be constructed for the purpose of climbing stairs by applying static and dynamic analysis techniques to optimize a design. This study provides the groundwork for this design, which can also serve as a basis for designing robots with other configurations.
Keywords: Track robot; Stair climbing